The path of the monster : the alien ‘other’ in science fiction and fantasy for young adults - Mavrick, Kandace Edana Vashti (Curtin University, 2009)
This thesis explores the way in which representations of the alien ‘other’ in SF for young adults are used as a tool for exploring the self/other dichotomy in the process of identity formation. It intends to develop a clear view of current, popular forms of representation of the alien other in this area, contribute to the still nascentcriticism of YA SF, and also operate as a constructive tool for creative writers working in this field.The exegesis is a meta-critical commentary on the YA SF field in general and the role of the character of the alien other within it in particular. It elucidates the preoccupation of the YA genre with ideas of identity and subjectivity and links this to developmental psychology, demonstrating the way that the self/other dichotomy in identity formation forms the basis of the character of the alien other and its expression in fiction and explaining the fascination and potential value of these characters to a young adult audience. It further looks at the way these characters are created and read and the limitations and possibilities that exist for authors in their construction, delineating the various archetypical constructions of these characters and exploring the ramifications of various methods of representation.The creative component of the thesis is a young adult fantasy novel, The Path of the Monster that explores the self/other dichotomy, challenging traditional binaries such as ‘good’ and ‘evil’ and questioning assumptions and understandings about identity and otherness. It particularly highlights the question ‘who is the monster?’, confronting expectations about the role of the other and simultaneously exploring the feeling of alienation that is common to the adolescent experience.